Fast Edge-Routing for Large Graphs - Dwyer, Tim; Nachmanson, Lev and (2009)
To produce high quality drawings of graphs with nodes drawn as shapes it is important to find routes for the edges which do not intersect node boundaries. Recent work in this area involves finding shortest paths in a tangent-visibility graph. However, construction of the full tangent-visibility graph is expensive, at least quadratic time in the number of nodes. In this paper we explore two ideas for achieving faster edge routing using approximate shortest-path techniques.